Weight Change After Korean Medicine Weight Management Treatment Combined with a Low-Carbohydrate Diet in Patients with Post-COVID-19 Condition: A Retrospective Multicenter Observational Study - Minwoo Bang; Suyong Shin; Jungsang Kim; Minwhee Kang; Donghun Lee; Junho Kim; Chunghee Kim; Jiyoung Son; Seonghyeon Jeon; Byungsoo Kang (Journal of Korean Medicine, 2026)
Objectives: To retrospectively describe weight change after Korean medicine weight management treatment combined with a low-carbohydrate diet (LCD) in patients with post-COVID-19 condition.Methods: This multicenter retrospective observational study used electronic medical records from eight Korean medicine clinics. Patients with post-COVID-19 condition who received Korean medicine weight management treatment for weight management and had paired baseline and follow-up body weight or body composition data were included. Primary outcomes were changes in body weight, body fat mass (BFM), and body mass index (BMI). Skeletal muscle mass (SMM), percent body fat (%BF), blood pressure, heart rate, laboratory parameters, handgrip strength, and adverse events were assessed as exploratory or descriptive outcomes. Paired comparisons were analyzed using the Wilcoxon signed-rank test.Results: Eleven patients were included. Body weight decreased from 69.66±16.50 kg to 64.14±15.55 kg (p=0.005), BFM from 27.03±8.72 kg to 22.66±6.58 kg (p=0.024), and BMI from 27.07±4.99 kg/m² to 24.85±4.08 kg/m² (p=0.007). Changes in SMM and %BF were not statistically significant. Other secondary variables, including blood pressure, heart rate, HbA1c, laboratory parameters, and handgrip strength, were limited or measured at heterogeneous time points and were therefore interpreted descriptively. Mild adverse events occurred in 5 of 11 patients (45.5%), with no severe adverse events.Conclusions: Korean medicine weight management treatment combined with LCD was associated with reduced body weight, BFM, and BMI in patients with post-COVID-19 condition, including some with baseline BMI below 23 kg/m². This study did not systematically evaluate long COVID-related symptom improvement. Larger prospective studies are needed.